1989
DOI: 10.1111/j.1943-278x.1989.tb00564.x
|View full text |Cite
|
Sign up to set email alerts
|

Economic Stress and Suicide: Multilevel Analyses

David Dooley,
Ralph Catalano,
Karen Rook
et al.

Abstract: Of the research on health and economic stress, the approach that has produced the strongest findings has been the aggregate time‐series analysis of unemployment and suicide rates. A review of the literature indicates that this aggregate work has been disputed on both methodological and interpretive grounds. To address these issues, two studies of the relationship between economic stress and suicide were conducted on the same population. The first, reported in this paper (Part 1), replicated the aggregate time‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…Our findings are consistent with these data in that both studies indicated that low self-efficacy had negative mental health consequences among women victimized by partners. Our data also are consistent with prior studies that showed a significant inverse association between social support and suicidal behavior (Durkheim, 1951; Heikkinen et al, 1994; Kaslow et al, 1998; Magne-Ingvar et al, 1992; Maris, 1997; Nisbet, 1996; Veiel et al, 1988) and studies that demonstrated a significant inverse relation between material resources and suicidal behavior (Dooley et al, 1989a, 1989b; Ferrada-Noli, 1997a; 1997b; Lester & Yang, 1997).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings are consistent with these data in that both studies indicated that low self-efficacy had negative mental health consequences among women victimized by partners. Our data also are consistent with prior studies that showed a significant inverse association between social support and suicidal behavior (Durkheim, 1951; Heikkinen et al, 1994; Kaslow et al, 1998; Magne-Ingvar et al, 1992; Maris, 1997; Nisbet, 1996; Veiel et al, 1988) and studies that demonstrated a significant inverse relation between material resources and suicidal behavior (Dooley et al, 1989a, 1989b; Ferrada-Noli, 1997a; 1997b; Lester & Yang, 1997).…”
Section: Discussionsupporting
confidence: 92%
“…It is important to increase abused women's ability to obtain social support and material resources because research has indicated that social support (Durkheim, 1951; Heikkinen, Aro, & Lonnqvist, 1994; Kaslow et al, 1998; Magne-Ingvar, Ojehagen, & Traskman-Bendz, 1992; Maris, 1997; Nisbet, 1996; Veiel, Brill, Hafner, & Weiz, 1988) and material resources (Dooley, Catalano, Rook & Serxner, 1989a, 1989b; Ferrada-Noli, 1997a, 1997b; Lester & Yang, 1997) may protect individuals from engaging in suicidal behavior. Although resources are always important for mental health, they are particularly crucial in times of stress (Hobfoll, 1988).…”
mentioning
confidence: 99%
“…The results were subject to vast criticism by Kasl (1979), Gravelle et al (1981), andWagstaff (1985), leading to much of Ruhm's work. 5 Durkheim (1897) first suggested that recessions are linked with higher suicide rates; subsequently, Brenner (1973Brenner ( , 1975, Dooley et al (1989), and Ruhm (2000, 2015 have documented a countercyclical relationship between suicides and the business cycle. 6 See Brenner and Mooney (1983) for a detailed discussion.…”
Section: Introductionmentioning
confidence: 99%